2022
DOI: 10.3390/ijms232112815
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Chromatin-Remodeling Factors in Cancer Cells: Promising Molecules in Cancer Therapy

Abstract: ATP-dependent chromatin-remodeling complexes can reorganize and remodel chromatin and thereby act as important regulator in various cellular processes. Based on considerable studies over the past two decades, it has been confirmed that the abnormal function of chromatin remodeling plays a pivotal role in genome reprogramming for oncogenesis in cancer development and/or resistance to cancer therapy. Recently, exciting progress has been made in the identification of genetic alteration in the genes encoding the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 223 publications
(194 reference statements)
0
8
0
Order By: Relevance
“…The role of CHAF1A in anti-cancer immunity remains unclear. Recently, regulators similar to CHAF1A in chromatin organization and remodeling have been reported to play critical roles in anticancer immunity, and have therefore become promising targets for cancer treatment [ 30 , 31 ]. Our GSEA showed that CHAF1A was associated with many DNA repair and metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The role of CHAF1A in anti-cancer immunity remains unclear. Recently, regulators similar to CHAF1A in chromatin organization and remodeling have been reported to play critical roles in anticancer immunity, and have therefore become promising targets for cancer treatment [ 30 , 31 ]. Our GSEA showed that CHAF1A was associated with many DNA repair and metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…There are ongoing developments in drugs that target genomic abnormalities of CRFs and combination therapies aimed at enhancing the therapeutic effects of anticancer drugs (41). In a previous study, the histone deacetylase inhibitor romidepsin, which targets CHD4, was demonstrated to suppress the progression of metastases in ovarian cancer both in vitro and in vivo (42).…”
Section: Discussionmentioning
confidence: 99%
“…We focus on chromatin remodeling in GI cancer as it has been recently revisited as an important disease modulator and therapeutic target by us and other researchers [ 14 , 15 ]. For the storage of genetic information, chromatin is composed of the nucleosome, which contains DNA and histones [ 15 , 16 ], and for proper regulation of gene expression, nucleosomes are modulated by a chromatin remodeling complex in an ATP-dependent manner [ 16 , 17 ]. These chromatin remodeling complexes include switch/sucrose non-fermentable (SWI/SNF), initiator of SWI (ISWI), chromodomain helicase DNA binding protein (CHD), and INO80 [ 16 ], which are frequently mutated and participate in tumorigenesis in GI cancers.…”
Section: Introductionmentioning
confidence: 99%